Clinical management of bleeding manifestations in a family with the thrombomodulin C1611>A (p.Cys537Stop) mutation - Serge Pierre-Louis; Johalene Rabout; Octavio Labrada; Fatima Radouani; Emeline Chonville; Beatrice Ferrey; Olivier Pierre-Louis; Yesim Dargaud (Research and Practice in Thrombosis and Haemostasis)
Background: The bleeding disorder described here is due to a heterozygous autosomal dominant C1611>A variant in the thrombomodulin (TM) gene that significantly elevates plasma TM levels, which enhances the activation of protein C. This activation inhibits factors VIIIa and Va, reducing thrombin generation and potentially leading to severe hemorrhagic manifestations. Key Clinical Question: What is the bleeding profile of patients with this rare condition? What are the most frequent clinical signs, and how can they be treated? Clinical Approach: We present a case study of an index patient with the TM C1611>A variant and his 20 family members. We detail the hemostatic strategies employed during various bleeding episodes and surgical procedures. Conclusion: Sharing clinical experiences is crucial for hematologists managing similar cases, as it provides valuable insights into effective treatment strategies.